-(5y+1)-(-4y-2)=0

Simple and best practice solution for -(5y+1)-(-4y-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5y+1)-(-4y-2)=0 equation:


Simplifying
-1(5y + 1) + -1(-4y + -2) = 0

Reorder the terms:
-1(1 + 5y) + -1(-4y + -2) = 0
(1 * -1 + 5y * -1) + -1(-4y + -2) = 0
(-1 + -5y) + -1(-4y + -2) = 0

Reorder the terms:
-1 + -5y + -1(-2 + -4y) = 0
-1 + -5y + (-2 * -1 + -4y * -1) = 0
-1 + -5y + (2 + 4y) = 0

Reorder the terms:
-1 + 2 + -5y + 4y = 0

Combine like terms: -1 + 2 = 1
1 + -5y + 4y = 0

Combine like terms: -5y + 4y = -1y
1 + -1y = 0

Solving
1 + -1y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -1y = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -1y = 0 + -1
-1y = 0 + -1

Combine like terms: 0 + -1 = -1
-1y = -1

Divide each side by '-1'.
y = 1

Simplifying
y = 1

See similar equations:

| 62=2b | | I=mv-mu | | 3(2n-7)-3=36 | | y=-(-2)+1 | | 5(x+-2)=2x+(x+6) | | 2x+30=8x+2 | | f(x)=2x^5-2x^4-29x^3-11x^2+51x+36 | | 5.8q-3.4-5.2q=-.4q-2.3 | | -8x+4y=-84 | | x*2x*(x+2)=90 | | 14+20x=16y | | -4x+3=3x+66 | | x+(1/10)=-(1/5) | | x-8.7=-3.4 | | p^2-4p-21=0 | | 10-10x=55-45x | | 16=12x+3x | | 16x^2+8x=3 | | 2+0.1(52-x)=1.8x-(0.4-2.7) | | 5(17)2/10 | | 12p+3q=66 | | 25x^2-5x-12=0 | | 5x+17=12x+67 | | 2y^2+y-20=0 | | 6=a/4-2 | | x(x+6)+48=(x+1)(x+7) | | (x+2/12)+(x-5/15) | | (2a+5)=(3a-2) | | 2x-2=5x-2 | | (x+2/12)+(x-5/15)=(2/3) | | 4x+x=6250 | | y=x^2+14x-5 |

Equations solver categories